1) (x + 6)(x - 6) = 0
x + 6 = 0 or x - 6 = 0
x = - 6 or x = 6
The equation does not have the same pair of solutions.
2) (x + 6)(x + 6) = 0
x + 6 = 0 or x + 6 = 0
x = - 6 twice
The equation has the same pair of solutions.
3) (x - 6)(x - 6) = 0
x - 6 = 0 or x - 6 = 0
x = 6 twice
The equation has the same pair of solutions.
4) (2x + 12)(2x - 12) = 0
2x + 12 = 0 or 2x - 12 = 0
2x = - 12 or 2x = 12
x = - 12/2 or x = 12/2
x = - 6 or x = 6
The equation does not have the same pair of solutions.
5) (2x - 12)(x - 12) = 0
2x - 12 = 0 or x - 12 = 0
2x = 12 or x = 12
x = 12/2 = 6 or x = 12
The equation does not have the same pair of solutions.
6) (x + 12)(x - 12) = 0
x + 12 = 0 or x - 12 = 0
x = - 12 or x = 12
The equation does not have the same pair of solutions.
7) (x + 12)(x - 6) = 0
x + 12 = 0 or x - 6 = 0
x = - 12 or x = 6
The equation does not have the same pair of solutions.